Les temporalités sociales : mise en marché et conflits - Jens Thoemmes (Temporalités)
This article presents the background, the purpose of analysis, transverse elements in the specialized literature, and introduces the contributions to this issue. The authors agree on the general finding that a change in social times has occurred. The first lesson we learn concerns the connection between the concepts of "time" and "market": financial markets in the first place, with the instability and new conceptions of time that accompany them, labor markets and employment next, as social times remain fundamentally dependent on the rationing of labor, product markets finally, that impose new means of production. The second lesson concerns the fact that time has become a commodity. In society, abandoning "traditional" times is achieved through negotiation at company level and within the family. The third lesson concerns the appearance of conflicts when temporality is driven into markets. Social groups oppose each other when they are prompted by social issues: workers against Sunday consumers; employers against the proponents of leisure time; welfare and safety against risk and volatility. The fourth lesson shows that the change is not limited to the sphere of economic and professional activity. This issue of Temporalités places the heart of change in the world of labor and, as we shall see, in varied work situations: the financial sector, self-employed IT engineers, services, shift work and collective bargaining. Nevertheless, the focus on work is insufficient. It is rather a question of recognizing that conceptions of time are deeply rooted in subjects’ experiences and representations.